PENGEMBANGAN APLIKASI SMART LOCK PADA SMART WATCH SISTEM OPERASI WEAR OS - Yulianto, Andik; Aripradono, Heru Wijayanto; Melvin, Melvin (LPPM UNIVERSITAS BINA INSAN, 2023)
Everyone needs a tool to lock their own property to prevent loss of said property. One type of locking tool that is commonly found is a padlock. Padlocks have gone through many design developments until modern times, people can now use padlocks wirelessly with Smart Padlock. Recent smartwatches have many sophisticated features and have adequate network capabilities, namely internet, Bluetooth and NFC. Because smartwatches are easy to carry anywhere and have the features and capabilities that smartphones should have, you can use them to make use of Internet of Things products, such as Smart Padlock, with just a watch.